Dampak Teknologi Komunikasi Shopee Live terhadap Affiliator Shopee: Pendekatan Technological Determinism - Lomanto, Reiner; Sandi, Rifki Aris (Universitas Muhammdiyah Yogyakarta, 2025)
This research analyzes the impact of Shopee Live on Shopee affiliates using the theory of technological determinism. Qualitative approach was used as the research method through in-depth interviews with six Shopee Live affiliates. The results showed that Shopee Live creates new jobs, influences interactions with customers, increases financial and social contributions, and enables flexible work patterns and a more comfortable lifestyle. Shopee Live brings socio-economic changes to society in the country's digital ecosystem, presenting both opportunities and challenges in the future. This research was significant for understanding the domestic digital economy, predicting the direction of its development, and anticipating it through adaptive and fair policies for digital workers.